Magnetic resonance imaging evaluation of the disc morphology of temporomandibular joint in patients with severe hemophilia - de Oliveira, Lays Assolini Pinheiro; Gomes, João Pedro Perez; Pimentel-Silva, Luciana Ramalho; de Castro Lopes, Sérgio Lúcio Pereira [UNESP]; Correa, Maria Elvira Pizzigatti; de Oliveira Lira, Adriana; Costa, Andre Luiz Ferreira (Springer Nature, 2023)
Objectives: This study aimed to assess the morphological differences in the articular disc (AD) between hemophilic patients and healthy individuals of the control group for further association with signs and symptoms. Methods: Fourteen severe hemophilic patients had their AD evaluated by magnetic resonance imaging (MRI). The morphological findings were compared to those of a control group consisting of 14 healthy individuals. MRI was used to evaluate all the components of the temporomandibular (TMJ), including the AD, resulting in sequential T1-weighted parasagittal images. All the images were acquired with teeth in maximum intercuspation position. Results: Morphological alterations showed significant statistical differences (P-value = 0.0068), whereas no statistical differences were found in the other variables, including TMJ pain, headache, bruxism and mouth opening limitation. In the group of non-hemophilic individuals, only two (14.29%) presented AD with non-biconcave features, whereas in the group of hemophilic patients, nine (64.29%) presented AD with a morphology other than biconcave. Conclusions: In patients with severe hemophilia, there seems to be a pattern of morphological alterations in the articular disc over time. The standard biconcave morphology of AD tends to change into other ones, particularly biplanar, hemiconvex and folded.
Keywords: Diagnostic imaging; Disc morphology; Hemophilia; Magnetic resonance imaging; Temporomandibular joint